Skills that Influence The Success of Marketing at The Social Security Administration of Employment (BPJS Ketenagakerjaan) - Saragih, Tarimantan Sanberto; Mahaganti, Fergie Stevi; Pramasanti, An Nisa; Putra, Mochammad Andika; Bagaskara, Septa; Augustin, Eldest; Fitriani, Kania (Eduvest - Journal of Universal Studies, 2023)
The Importance of marketing makes marketing strategy a crucial aspect that needs attention. Various marketing strategies need to be implemented, one of which is through the sales force. BPJS Ketenagakerjaan requires a sales force to provide information and increase participation in BPJS Ketenagakerjaan. To enhance the addition of social security employment participants, a membership team needs human resource skills, namely soft skills and hard skills. The purpose of this research is to determine the skills that influence the success of the BPJS Ketenagakerjaan membership team. The research method used is a case study method with a qualitative approach through the sales forces productivity program. The results show that BPJS Ketenagakerjaan identifies resources that influence the success of marketing through the salesforce, namely 3 basic mentalities, 4 interpersonal skills, and 5 practical abilities, known as the DNA 345 Salesforce Success Factors. Mentalities include resilience, adaptability, and coherence. Interpersonal skills encompass approaching, influencing, conveying ideas, negotiating, and empathetic listening. Practical abilities include market analysis, building networks, product marketing, customer retention, and problem-solving. The Sales Force Productivity Program improves the performance of the salesforce in the marketing strategy of BPJS Ketenagakerjaan.